Barriers to reporting workplace violence: a qualitative study of nurses’ perceptions in tertiary care settings - Nadia Bassuoni Elsharkawy; Abeer Nuwayfi Alruwaili; Osama Mohamed Elsayed Ramadan; Majed Mowanes Alruwaili; Ali Alhaiti; Enas Mahrous Abdelaziz (BMC Nursing)
Abstract Background Workplace violence (WPV) remains a formidable concern among nurses worldwide, with up to 60% in Saudi Arabia reportedly experiencing some form of aggression. In tertiary care hospitals, robust hierarchies and cultural norms intensify underreporting, thwarting evidence-based prevention and obscuring vital data. Aim This qualitative study investigated the perceived barriers to WPV reporting among nurses in tertiary care settings in the Aljouf region of Saudi Arabia, specifically addressing how organizational and cultural factors converge to discourage formal incident reporting. Methods A qualitative descriptive design was employed, guided by Ajzen’s Theory of Planned Behavior and the Social Ecological Model. Thirty-six registered nurses, purposively sampled from three tertiary hospitals, participated in six semi-structured focus groups conducted in Arabic or English, depending on participant preference. Data were thematically analyzed in NVivo, with methodological rigor ensured through triangulation and inter-coder reliability. Results Three principal themes emerged: (1) Emotional and Psychological Barriers (78%), encompassing distress, anxiety, and fears of professional blame; (2) Organizational Ineffectiveness (65%), marked by convoluted reporting processes and perceived managerial indifference; and (3) Cultural and Hierarchical Influences (57%), reflecting deference to authority and normalization of violence. These themes illustrate how attitudes, subjective norms, and perceived behavioral control shaped by socio-cultural dynamics collectively contribute to persistent underreporting. Conclusions Mitigating WPV underreporting in Saudi tertiary care hospitals requires streamlined, user-friendly reporting channels, leadership accountability, and holistic psychosocial support. Implementing interprofessional education aimed at dismantling hierarchical imbalances can foster a zero-tolerance ethos toward violence. Longitudinal and comparative research should further examine evolving reporting behaviors to refine context-specific, culturally attuned strategies for addressing WPV. Clinical trial number Not applicable.